A poly(l-glutamic acid)-combretastatin A4 conjugate for solid tumor therapy: Markedly improved therapeutic efficiency through its low tissue penetration in solid tumor. (15th April 2017) - Liu, Tianzhou; Zhang, Dawei; Song, Wantong; Tang, Zhaohui; Zhu, Jiaming; Ma, Zhiming; Wang, Xudong; Chen, Xuesi; Tong, Ti
Graphical abstract: Abstract: Combretastatin A4 (CA4) is a leading agent in vascular disrupting strategies for tumor therapy. Although many small-molecule prodrugs of CA4 have been developed to improve its solubility, the overall therapeutic efficiency is moderate. A key reason for this is the reversible effect that CA4 has on tubulin as well as its rapid clearance from plasma and tissues. In this study, we proposed a poly(l- glutamic acid)-CA4 conjugate (PLG-CA4) nanomedicine to fulfill the requirements for fully liberating the potential of CA4 on tumor therapy. Enhanced accumulation and retention of CA4 in tumor tissue, especially, high distribution and gradual release around tumor blood vessels resulted in prolonged vascular disruption and markedly enhanced therapeutic efficiency. We examined and compared the therapeutic effect of PLG-CA4 and commercial combretastatin-A4 phosphate (CA4P) in a murine colon C26 tumor. PLG-CA4 showed significantly prolonged retention in plasma and tumor tissue. Most importantly, the PLG-CA4 was mainly distributed around the tumor vessels because of its low tissue penetration in solid tumor. Pathology tests showed that PLG-CA4 treatment resulted in persistent vascular disruption and tumor damage 72 h after a single injection, this in contrast to CA4P treatment, which showed quick relapse at an equal dose. Tumor suppression tests showed that PLG-CA4 treatment resulted in a tumor suppression rate of 74%, which indicates a significant advantage when compared to tumor suppression rate of the CA4P group, which was 24%. This is the first time that an advantage of the polymeric CA4 nanomedicine with low tissue penetration for solid tumor therapy has been shown. Thus, the results presented in this study provide a new idea for enhancing the tumor therapeutic effect of vascular disrupting agents. Statement of Significance: Nanomedicine usually has low tissue penetration in solid tumors, which limits the efficacy of nanomedicine in most cases. But herein, we demonstrate a nanosized vascular disruptive agent (VDA) PLG-CA4 has supper advantages over small molecular combretastatin-A4 phosphate (CA4P) because the PLG-CA4 was mainly distributed around the tumor vessels due to its low tissue penetration in solid tumor.